"\\frac{dx}{x^3-3xy^2}=\\frac{dy}{y^3+3x^2y}=\\frac{dz}{2z(x^2+y^2)}"
"\\frac{dy}{dx}=\\frac{y^3+3x^2y}{x^3-3xy^2}"
This is a homogeneous differential equation.
Let "y\/x=v, y=xv, dy\/dx=v+x(dv\/dx)"
Then:
"v+x\\frac{dv}{dx}=\\frac{(xv)^3+3x^3v}{x^3-3x^3v^2}=\\frac{v^3+3v}{1-3v^2}"
"x\\frac{dv}{dx}=\\frac{v^3+3v}{1-3v^2}-v=\\frac{4v^3+2v}{1-3v^2}"
"\\frac{1}{2}\\intop\\frac{1-3v^2}{v(2v^2+1)}dv=\\intop \\frac{dx}{x}"
"\\frac{1-3v^2}{v(2v^2+1)}=\\frac{A}{v}+\\frac{Bv+C}{2v^2+1}"
"A(2v^2+1)+v(Bv+C)=1-3v^2"
"2A+B=-3"
"A=1"
"C=0"
"B=-3-2A=-5"
"\\frac{1-3v^2}{v(2v^2+1)}=\\frac{1}{v}-\\frac{5v}{2v^2+1}"
"\\intop\\frac{v}{2v^2+1}dv=\\frac{1}{2}\\intop\\frac{d(v^2)}{2v^2+1}dv=\\frac{ln(2v^2+1)}{4}"
"\\frac{lnv}{2}-\\frac{5ln(2v^2+1)}{8}=lnx+lnc_1"
"ln(\\frac{v^{1\/2}}{(2v^2+1)^{5\/8}})=ln(c_1x)"
"\\frac{(y\/x)^{1\/2}}{x(2(y\/x)^2+1)^{5\/8}}=c_1"
"\\frac{dx\/x+dy\/y+dz\/z}{6x^2}=-\\frac{3(dx\/x-dy\/y+dz\/z)}{6y^2}=\\frac{dz}{2z(x^2+y^2)}"
"\\frac{dx\/x+dy\/y+dz\/z-3(dx\/x-dy\/y+dz\/z)}{6x^2+6y^2}=\\frac{3dz\/z}{6(x^2+y^2)}"
"dx\/x+dy\/y+dz\/z-3(dx\/x-dy\/y+dz\/z)=3dz\/z"
"4dy\/y-2dx\/x=5dz\/z"
"4lny-2lnx=5lnz+lnc_2"
"ln(y^4\/x^2)=ln(c_2z^5)"
"\\frac{y^4}{x^2z^5}=c_2"
The general integral:
"\\phi(\\frac{(y\/x)^{1\/2}}{x(2(y\/x)^2+1)^{5\/8}}, \\frac{y^4}{x^2z^5})=0"
Comments
Leave a comment